Inflammation and platelet hyperresponsiveness in coronary artery disease and the influence of Talin-1/αIIbβ3-mediated bidirectional signaling pathway - Shi, Shengnan; Gao, Jiaming; Zhang, Yehao; Zhan, Min; Tan, Zhanfei; Wang, Peili; Fu, Jianhua; Liu, Jianxun (Frontiers in Pharmacology, 2025)
BackgroundWhile platelet hyperreactivity constitutes an independent risk factor for major adverse cardiovascular events (MACEs) in coronary artery disease, its molecular underpinnings remain poorly characterized. Recent advances in transcriptomic profiling have revealed potential associations with specific RNA signatures. Through systematic bioinformatics analysis of differential gene expression patterns and pathway activation in CHD patients, this study aims to elucidate key molecular regulators of platelet hyperactivity, establishing a theoretical framework for developing precision therapeutic strategies to mitigate post-CHD complications.MethodsThis randomized controlled study included 16 CHD patients and 16 healthy controls. Inflammation markers, platelet aggregation function, and CD62p levels were assessed using flow cytometry. Mitochondrial morphology and organelles were observed using scanning electron microscopy and transmission electron microscopy. Genes related to symptom alteration between CHD patients and healthy controls were identified using the criteria of p < 0.05. The molecular correlations of these genes were analyzed using a comprehensive perspective that included Gene Ontology (GO) biological process and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Western blot and correlation analyses were also conducted to validate the expression and diagnostic value of the DEGs.ResultsCHD patients exhibited alterations in platelet organelles ultrastructure, heightened platelet activation and aggregation, and disturbance of the inflammatory equilibrium. RNA sequencing demonstrated distinct changes in the gene expression profiles of circulating platelets from CHD patients. The increase in platelet activation and aggregation could be partially associated with the upregulation of the Talin-1 and αIIbβ3 proteins expression.ConclusionAbnormal transcription and platelet activation occur after CHD onset, and upregulation of the Talin-1/αIIbβ3-mediated bidirectional signaling pathway are the primary pathological features.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR2100041998.